Improving Roofs to Reduce Energy and Protect Occupants from Climate Change - D’Agostino, Delia; Parker, Danny (CLIMA 2022 conference, 2022)
Refurbishing existing buildings to reduce energy use is a priority worldwide to reduce greenhouse gas emissions. Millions of buildings have poorly insulated old roofs with large roof surface areas. Covered by photovoltaic (PV) arrays, these roofs could potentially provide significant renewable energy generation. Uninsulated, they increase needs for heating and cooling, while also posing health risks for top-floor occupants during summer heat waves. Such heat waves look to become increasingly common with future climate change. Suspended air conditioning from power interruptions are likely due to excessive system electric demand, earthquake or storm. We analyze an uninsulated apartment building in Milan for several scenarios to save energy while improving occupant comfort in top floor apartments. We evaluate three strategies: added roof insulation, increased roof solar reflectance and covering PV arrays above the roof. We estimate heating and cooling energy savings as well daily temperatures of a roof-adjacent top floor flat under peak summer conditions. We evaluate using current weather TMY 2018 files as well as another morphed to anticipated 2060 weather for the 90% IPCC scenario which represents extreme warming.